Services, industry evolution, and the competitive strategies of product firms - Cusumano, Michael A.; Kahl, Steven J.; Suarez, Fernando F. (Strategic Management Journal, 2015)
Services of different types have become increasingly important for product firms. While these firms mainly focus on products, managers and researchers lack a comprehensive framework to understand when to make significant investments in particular kinds of services. We identify three categories of product‐related services from a product firm—smoothing and adapting services, which complement products, and substitution services, which enable customers to pay for the use of a product without buying the product itself. We develop propositions about the relative level of these different kinds of services vis‐a‐vis industry evolution, as well as suggest how these services affect industry structure. We draw upon various literatures, though we conclude that the relationship between products and services is more complex and richer than any one literature suggests . Copyright © 2014 John Wiley & Sons, Ltd.